Investigating Quality Dimensions of Hospitality Higher Education: From Students' Perspective. Issue 2 (2nd April 2016) - Lee, Myong Jae; Huh, Chang; Jones, Margie Ferree
ABSTRACT: It is essential to identify and evaluate the important quality attributes of hospitality higher education on a continuing basis. This assessment helps administrators to ensure the quality of programs and attract top talent. This empirical research delineates quality dimensions of hospitality higher education from the perspectives of hospitality management students. A total of 314 usable responses were collected from four different hospitality management programs in the United States. Exploratory factor analysis identified five quality dimensions of hospitality higher education. Results of group comparisons using demographic variables provide meaningful implications for educators and administrators in U.S. hospitality higher education.